(3GdJYGRi hGdeQGKis - (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, GdeHQO , CHh GdYHGS,J (B286 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMi Gdbjhe bGd CHh GdYHGS OYGfG Edi JCdja gPG GdcJGH GLJdGH eMGSf ef Jcde ai CSHGH GdehJ ef GdehGYX hGdJYGRI GdeQGKi s
(3BNQgG (B:s
(3hbd ddCYGOi CYdfhG ChOYhG ShGA YdjfG GdeSJSQ hPh GdLgQ Je GdcJGH HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B114s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs